Effects of Herbaceous Root Growth on Soil Resistance to Erosion under Different Planting Densities - LIU Junyang; ZHOU Zhengchao; HAN Weixiao (Shuitu Baochi Xuebao)
［Objective］ To explore the effects of roots on soil consolidation and erosion reduction under different planting densities. ［Methods］ Typical herbaceous plants, including ryegrass (Lolium perenne) and alfalfa (Medicago sativa) on the Loess Plateau were selected as the research objects. By setting three planting densities, i.e. 100, 300 and 500 plants/m2, the effects of plant root growth on soil resistance to erosion were studied experimentally. ［Results］ During the observation period, the root characteristics showed a trend of rapid increase at first and then slow decrease, with those of ryegrass and alfalfa being the best in medium and high planting-density plots, respectively. Driven by root growth, soil organic matter content showed an increasing trend, with that of ryegrass and alfalfa increasing the most in medium and high planting-density plots, which increased by 2.44 g/kg and 1.84 g/kg, respectively. Under the combined influence of changes in root and soil characteristics, rill erodibility index decreased rapidly at first and then showed a fluctuating change during the observation period, while soil critical shear stress did not show a stable trend. Ryegrass roots had the best erosion reduction effect in the medium planting-density plot, where rill erodibility index decreased by 18.86 s/m. Alfalfa roots had the better erosion reduction effect in the medium and high planting-density plots, where rill erodibility index decreased by 13.42 s/m and 10.82 s/m, respectively. ［Conclusion］ Considering the effect of planting density on roots and soil characteristics, the medium density (300 plants/m2) and high density (500 plants/m2) planting patterns are suitable for soil erosion control by growing ryegrass and alfalfa, respectively.